2006
DOI: 10.3132/dvdr.2006.029
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone increases LDL particle size and buoyancy and decreases C-reactive protein in patients with type 2 diabetes on statin therapy

Abstract: A substantial number of individuals with type 2 diabetes mellitus (T2DM) demonstrate a predominance of small dense low-density lipoprotein (sdLDL), which is associated with an increased risk of cardiovascular disease (CVD). In some cases, sdLDL persists after treatment with a statin to reduce levels of LDL. The effect of the addition of a thiazolidinedione, rosiglitazone (RSG) (4 mg/day or 8 mg/day) to statin therapy on LDL phenotype and C reactive protein (CRP) levels was investigated in a 12-week, placebo-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
(41 reference statements)
1
18
0
Order By: Relevance
“…These effects were achieved mainly through the action of inhibiting the macrophage activation [12,23,24]. A recent study performed on diabetic patients with statin use demonstrated that TZD can significantly lower the CRP level by more than 45% [25]. A meta-analysis also documented that treatment with TZDs significantly decreased the serum CRP level.…”
Section: Anti-inflammatory Anti-oxidant and Other Pleiotropic Effectmentioning
confidence: 96%
“…These effects were achieved mainly through the action of inhibiting the macrophage activation [12,23,24]. A recent study performed on diabetic patients with statin use demonstrated that TZD can significantly lower the CRP level by more than 45% [25]. A meta-analysis also documented that treatment with TZDs significantly decreased the serum CRP level.…”
Section: Anti-inflammatory Anti-oxidant and Other Pleiotropic Effectmentioning
confidence: 96%
“…Rosiglitazone significantly increased LDL buoyancy as well as LDL particle size in 72 patients with type 2 diabetes mellitus in a 12 week, placebo-controlled study [89]. Another study of the same duration, but open-label, in 18 diabetic patients confirmed an increase in LDL size, with less small, dense LDL particles.…”
Section: Antihyperglycemic Treatments With Effects On Ldl Particle DImentioning
confidence: 57%
“…Of the 13 trials with conclusions that did not favor the test (glitazone) drug, 4 had glycemic control results favoring the glitazone. Moreover, there were 13 trials where the results reported for glycemic control were inconsistent with the conclusions of the papers [29][41]. Specifically, in 9 trials, favorable conclusions were reported yet glycemic control results were either similar or unfavorable to the comparator [29][37], though notably two trials were focused on lipid effects or inflammatory markers [36], [37].…”
Section: Resultsmentioning
confidence: 99%